2021
DOI: 10.1108/s1530-353520210000016010
|View full text |Cite
|
Sign up to set email alerts
|

The Policy Measures Used by the Hong Kong Government to Respond to the Adult Worker Model and the Male-breadwinner Model

Abstract: There have been ongoing discussions on the male-breadwinner model and the adult worker model in research on family-related welfare policies. The male-breadwinner model posits that men work full-time outside the home and women take on domestic work. The adult worker model suggests that women and men should be equally expected to play an active role in the paid labor market. The aim of this article is to explore the responses made by the Hong Kong government to these two models. We meet this aim by presenting tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In particular, older women deserve additional attention. Due to traditional gendered expectations, women are often expected to meet the care needs in the family, which hamper their career development (Kroger, 2011; Yu et al, 2021). Previous research has shown that compared with men, women tend to encounter greater difficulties in saving sufficient pension incomes for retirement through the local work-based pension scheme (the Mandatory Provident Fund) in Hong Kong (Yu et al, 2021).…”
Section: The Study Of Older Women’s Responses To Mask-related Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, older women deserve additional attention. Due to traditional gendered expectations, women are often expected to meet the care needs in the family, which hamper their career development (Kroger, 2011; Yu et al, 2021). Previous research has shown that compared with men, women tend to encounter greater difficulties in saving sufficient pension incomes for retirement through the local work-based pension scheme (the Mandatory Provident Fund) in Hong Kong (Yu et al, 2021).…”
Section: The Study Of Older Women’s Responses To Mask-related Issuesmentioning
confidence: 99%
“…Chiu and Wong (2005: 89) suggest that traditional Chinese family values, such as love for one’s family and the importance of collective responsibility, have been used by the Hong Kong government as ‘a means to contain social welfare costs’ to justify the residual welfare model. Other scholars also argue that by stressing the family and the market as important channels for meeting people’s needs, the government can lower people’s expectations on public policy and avoid political challenges (Yu et al, 2021). The analysis of the social policy in Hong Kong is influenced significantly by the Productive Welfare Capitalism Thesis (Holliday, 2000).…”
Section: The Study Of Older Women’s Responses To Mask-related Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the unsupported adult worker model, the supported adult worker model stresses that, if a government wants to encourage women to take part in formal employment, it should employ a proactive strategy, which is associated with the principle of gender equality [ 3 ]. Governments favouring this strategy are expected to actively support women to balance their labour force participation and care duties [ 8 ]. Studies show that an important way to do so is to reduce the costs of care provision borne by the family through the provision of care support measures, including subsidised childcare services, paid maternity leave benefits, and paid father-specific leave benefits [ 1 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%